2019
DOI: 10.1002/14651858.mr000051
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring strategies for clinical intervention studies

Abstract: This is a protocol for a Cochrane Review (Methodology). The objectives are as follows: The main objective of this systematic review of prospective empirical studies is to evaluate the benefits and disadvantages of trial-specific, risk-based monitoring strategies compared with a traditional intensive on-site monitoring strategy or other monitoring strategies for randomized and non-randomized prospective intervention studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Many different comparisons have been made between various monitoring strategies and the majority have found that the differences in strategies are noninferior. In the latest study in 2021, Klatte et al published a Cochrane review showing no evidence that any RBM strategy is inferior to extensive monitoring when looking at errors 11 . For a risk‐based approach to be truly risk‐based, the focus must be on risks to the participants, the study outcome and the reliability of data and not just on errors in general.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many different comparisons have been made between various monitoring strategies and the majority have found that the differences in strategies are noninferior. In the latest study in 2021, Klatte et al published a Cochrane review showing no evidence that any RBM strategy is inferior to extensive monitoring when looking at errors 11 . For a risk‐based approach to be truly risk‐based, the focus must be on risks to the participants, the study outcome and the reliability of data and not just on errors in general.…”
Section: Discussionmentioning
confidence: 99%
“…In the latest study in 2021, Klatte et al published a Cochrane review showing no evidence that any RBM strategy is inferior to extensive monitoring when looking at errors. 11 For a risk-based approach to be truly risk-based, the focus must be on risks to the participants, the study outcome and the reliability of data and not just on errors in general. The various RBM tools available on the market have different interpretations of risks to a CT, as published by Fneish, who evaluated 18 protocols across six different tools and found variation on the risk categorization between the tools.…”
Section: Many Different Comparisons Have Been Made Between Variousmentioning
confidence: 99%
See 2 more Smart Citations
“…Though at reduced levels through risk-based approaches, SDV is still being used as a major strategy to identify errors and assure high-quality data. [26][27][28] This thinking must change. As a fallible manual process, SDV was never capable of assuring high-quality data from a fallible source.…”
Section: Introductionmentioning
confidence: 99%